A Cross Sectional Clinical Analysis of Hemiplegia (Pakkavatham) Related to Diabetes Mellitus (Mathumeham) and Hypertension (Erathakothippu) - Sujeethasai, K.; Manoharan, A.; Rajarajeshwari, A. (Journal of Complementary and Alternative Medical Research, 2019)
Background: Stroke (Pakkavatham) is the second leading mortality cause in global and death occurrence rates, rising in middle to older aged people. This condition is increased due to the dietary pattern and lifestyle modifications. Aim: To determine about the interrelationship of Type II Diabetes Mellitus DM) and Systemic Hypertension (SHT) associated with hemiplegia. Study Design: Cross Sectional Descriptive Observational Study. Place and Duration of Study: This study work was carried out in 50 patients in Government Siddha Medical College and Hospital, Palayamkottai, Tirunelveli, Tamil Nadu from April 2019 to September 2019. Materials and Methods: This study was carried in 50 subjects (30 subjects in Out Patient Department (OPD) and 20 subjects in In Patient Department (IPD) were randomly selected and the data were collected by interviewing with a structured questionnaire. The ethical clearance was attained from the Institutional Ethical Committee. Results: The highest incidence was male patients (38%) than female patients, the affected age group was 51-60 years. The prevalence was seen in male alcoholic consumers (46%), chronic smokers (44%) respectively. The incidence was mostly seen in hypertensive (70%) and nondiabetic (46%) male patients. Among the 50 patients, 14 patients (28%) had both SHT and DM. The most prevalence was seen in hypertensive patients than DM or SHT combined with DM patients. The moderate improvement was seen in the patients (32%) of control blood pressure and serum glucose level. Conclusion: The SHT may influence in the prevalence of Pakkavatham and control blood pressure and serum glucose level may be improved the good prognosis in Pakkavatham patients.
Keywords: Pakkavatham; Hemiplegia; Type II diabetes mellitus; Mathumeham; Systemic Hypertension; Erathakothippu